Gold futures prices: An investigation into the theories of storage and forecast power and premium - M. J. Page (South African Journal of Business Management, 1990)
There are two principal theories of commodity futures prices. The theory of storage, which explains the difference between contemporaneous futures and spot prices (the basis) in terms of interest rates, warehousing costs, and convenience yields, and the theory of forecast power and premium, which is based on the assumption that the futures price is a biased estimate of the expected spot price. This research paper examines the applicability of the two theories to the pricing of short term gold futures contracts. The findings suggest that, in terms of the theory of storage, the basis variability is explained principally by interest rate changes for contracts of between three and six months duration, while for one-month contracts varying convenience yields appear to be the dominant factor. The low basis variability of gold futures contracts results in inconclusive findings with respect to the theory of forecast power and premium. There is, however, evidence to suggest that the basis contains some ability to predict the expected premium or bias.
Keywords: 650